A smart cascaded H-bridge multilevel inverter with an optimized modulation techniques increasing the quality and reducing harmonics - Babkrani, Youssef; Naddami, Ahmed; Hilal, Mohamed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
The world community relied heavily on fossils energies but just after the big oil crisis the use of renewable energy has greatly increased and has become the main interest of many countries for its many advantages such as: minimal impact on the environment, renewable generators requiring less maintenance than traditional ones and it has also a great impact on economy. It is easy to get charmed by the advantages of using the renewable resources but we must also be aware of their disadvantages. One of the major disadvantages is that the renewable energy resources are intermittent and thus they have led scientists to develop new semiconductor power converters among which are the multilevel inverter. In this paper a new smart multi-level inverter is proposed so as to increase its levels according to the user’s needs and also to avoid the impact of shades and the intermittence on photovoltaic panels. We also propose a modification on the multicarrier aiming to reduce the harmonics. This modification introduces a sinusoidal wave compared with trapezoidal multi-carrier to generate the pulses. In order to obtain the line voltages and the total harmonic distortions (THD) MATLAB/SIMULINK is used.